GRIM-19 and p16(INK4a) Synergistically Regulate Cell Cycle Progression and E2F1-responsive Gene Expression - Sun, Peng (American Society for Biochemistry and Molecular Biology, 2010)
GRIM-19 (Gene associated with Retinoid-IFN-induced Mortality-19) was originally isolated as a growth suppressor in a genome-wide knockdown screen with antisense libraries. Like classical tumor suppressors, mutations, and/or loss of GRIM-19 expression occur in primary human tumors; and it is inactivated by viral gene products. Our search for potential GRIM-19-binding proteins, using mass spectrometry, that permit its antitumor actions led to the inhibitor of cyclin-dependent kinase 4, CDKN2A. The GRIM-19/CDKN2A synergistically suppressed cell cycle progression via inhibiting E2F1-driven gene expression. The N terminus of GRIM-19 and the fourth ankyrin repeat of CDKN2A are crucial for their interaction. The biological relevance of these interactions is underscored by observations that GRIM-19 promotes the inhibitory effect of CDKN2A on CDK4; and mutations from primary tumors disrupt its ability to interact with GRIM-19 and suppress E2F1-driven gene expression.